Delayed Healing of Tooth Extraction Sockets with Ramucirumab Use - Yosuke Iijima; Miki Yamada; Shunsuke Hino; Motohiko Sano; Takahiro Kaneko; Norio Horie (Hindawi Limited, 2020)
Objective. An angiogenesis inhibitor can cause medication-related osteonecrosis of the jaw (MRONJ). To our knowledge, there has been no report that an angiogenesis inhibitor causes delayed healing of tooth extraction socket. Here, we describe a case of delayed healing of tooth extraction sockets associated with an angiogenesis inhibitor, ramucirumab, which showed characteristics similar to MRONJ. Materials and Methods. A 76-year-old male patient, who was diagnosed with gastric cancer with liver metastasis, received tooth extraction twice during continuous chemotherapy comprising paclitaxel and ramucirumab. Results. The first extraction was performed 30 days after ramucirumab discontinuation without complication. The second extraction was conducted without ramucirumab discontinuation. Although tooth socket healing was finally achieved, it took about 150 days. Discussion. This case was considered to be delayed healing of dry sockets rather than MRONJ due to ramucirumab. Dentists and oral surgeons need to be aware that angiogenesis inhibitors can cause not only MRONJ but also dry sockets after tooth extraction.